Cataplexy and sleep disorders in Niemann-Pick type C disease - Nevsimalova, Sona; Malinova, Vera (Current neurology and neuroscience reports, 2015)
Niemann-Pick disease type C (NP-C) is a rare and progressive autosomal recessive disease leading to disabling neurological manifestation and premature death. The disease is prone to underdiagnosis because of its highly heterogeneous presentation. NP-C is characterized by visceral, neurological, and psychiatric manifestation, and its clinical picture varies according to age at onset. Although cataplexy is one of its characteristic symptoms, particularly in the late infantile and juvenile form, sleep disturbances are described only exceptionally. A combination of splenomegaly, vertical supranuclear gaze palsy, and cataplexy creates a most useful suspicion index tool for the disease. In adolescent and adult patients, when intellectual deterioration progresses and emotional reactions become flat, cataplexy usually disappears. Pathological findings in the brainstem in NP-C mouse model are compatible with the patients' symptoms including cataplexy. The authors observed cataplexy in 5 (3 with late infantile and 2 with juvenile form) out of 22 NP-C cases followed up in the past 20 years.
Keywords: Niemannova-Pickova nemoc typu C; Cataplexy; poruchy spánku a bdění; Niemann-Pick Disease, Type C; Sleep Wake Disorders; lidé; Animals; zvířata; kataplexie; Humans